The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
S.Yu. Serebrova – Comparative clinical pharmacology of modern proton pump inhibitors.A.O. Bueverov – Apoptosis of hepatocytes and peripheral blood leukocytes at chronic hepatites B and C.